ANALISIS MARGIN PEMASARAN TELUR AYAM RAS PADA USAHA PETERNAKAN âCAHAYA ARIS MANISâ DI DESA LANGALESO KECAMATAN DOLO KABUPATEN SIGI - Fadil, Muh; Kalaba, Yulianti; Kalaba, Yulianti; Muiis, abdul (AGROTEKBIS, 2017)
The purpose of the study was to determine the marketing channels, marketing margin, part of the price received by farmers and marketing efficiency. Determination of the respondents to the farm was done intentionally (purposive). Total respondents two people consisting of 1 leader and 1 employee with the consideration that the respondents have to know the flow of the marketing of the products produced. Respondent traders used assessment method (Tracing Method), in order to obtain each 2 collectors and 1 retailers. The results showed that there are two channels of marketing eggs in the effort "breeder laying hens on the farm" Aris Light Sweet "as follows: 1). Breeders - Traders Gatherer - Retailer - Consumer. 2). Breeders - Traders Gatherer/retailer - Consumer. Margin on the first channel of IDR.9,600 and a second channel IDR.5,400. Section prices received by farmers in the first marketing channel by 91% and the second channel by 93%. Section prices received by farmers on the second channel ar greater, with the efficiency of 4,5%. Compared with the first channel with the efficiency of 4,7%. The results also showed that the efficiency of the marketing channels more efficiently. Key Words : Efficiency, marketing , margin , part price.